Complementary and Integrative Interventions for Improving Fatigue and Quality of Life in Adults Receiving Hemodialysis: A Review - Ade Komariah; Erna Rochmawati (Universitas Aisyah Pringsewu, 2022)
Fatigue is a common symptom experienced by patients receiving hemodialysis and can significantly decrease patients' quality of life. Some studies have been conducted using complementary and integrative interventions, but a synthesis of the available evidence is still limited. The review aimed to map complementary and integrative interventions and summaries the potential benefit in fatigue and quality of life. Scoping review framework from Joanna Briggs Institute was adopted. A defined search strategy was used in reviewing literature from Emerald, Pro Quest, PubMed, Science Direct, and Scopus. Studies were selected for further evaluation based on relevance to the inclusion criteria. Findings were then summarized and reported based on PRISMA for Scoping Review guidelines. A total of 14 studies from 1128 searches were included in the review. Non-pharmaceutical interventions included educational-based interventions, aromatherapy, massage, and breathing exercises. Many studies demonstrated that the interventions improved fatigue status and quality of life. Complementary interventions provide benefits for patients in managing fatigue and improving their quality of life. The findings of this review will contribute to integrating complementary therapy into the nursing practice. Additional studies are needed to clarify the potential value of available complementary and integrative interventions in the hemodialysis setting. Abstrak: Kelelahan sebagai gejala umum yang dialami oleh pasien yang menerima hemodialisis dapat secara signifikan menurunkan kualitas hidup pasien. Beberapa penelitian telah dilakukan dengan menggunakan intervensi komplementer dan integratif tetapi sintesis pada bukti yang tersedia masih terbatas. Tinjauan ini bertujuan untuk memetakan intervensi komplementer dan integratif dan merangkum potensi manfaat dalam kelelahan dan kualitas hidup. Kerangka kerja tinjauan pelingkupan dari Joanna Briggs Institute diadopsi. Strategi pencarian yang ditentukan digunakan dalam meninjau literatur dari Emerald, Pro Quest, PubMed, Science Direct, dan Scopus. Studi dipilih untuk evaluasi lebih lanjut berdasarkan relevansi dengan kriteria inklusi. Temuan kemudian diringkas dan dilaporkan berdasarkan pedoman PRISMA for Scoping Review. Sebanyak 14 studi dari 1128 pencarian dimasukkan dalam ulasan. Intervensi non-farmasi termasuk intervensi berbasis pendidikan, aromaterapi, pijat, olahraga dan latihan pernapasan. Banyak penelitian menunjukkan bahwa intervensi meningkatkan status kelelahan dan kualitas hidup. Intervensi komplementer memberikan manfaat bagi pasien dalam mengelola kelelahan dan meningkatkan kualitas hidup. Temuan ulasan ini akan berkontribusi pada integrasi terapi komplementer dalam praktik keperawatan. Studi tambahan diperlukan untuk memperjelas nilai potensial dari intervensi komplementer dan integratif yang tersedia dalam pengaturan hemodialisis.